2016
DOI: 10.1002/2016gl070075
|View full text |Cite
|
Sign up to set email alerts
|

An important missing source of atmospheric carbonyl sulfide: Domestic coal combustion

Abstract: Carbonyl sulfide (COS), carbon monoxide (CO), and sulfur dioxide (SO2) emissions generated from prevailing domestic coal stoves fueled with raw bituminous coal were studied under alternation cycles of flaming and smoldering combustion. The measurements in the laboratory and the farmer's house indicated that COS and CO emissions mainly occurred under the condition of flame extinguishment after coal loading, whereas SO2 emissions were mainly generated through combustion with flame. The COS emission factors for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Observed atmospheric surface mixing ratios from global and hemispheric averages of NOAA air monitoring sites (Montzka et al, ), as well as annually averaged tropospheric mixing ratios from Jungfraujoch (Lejeune et al, ), show a moderate decline in the 1990s followed by similarly moderate growth in the 2000s (both approximately 1% year −1 ), with relatively little interannual variation. These time trends have been attributed to trends in the anthropogenic inventory, driven by a decline in residential coal in the early 1990s and the decline and growth of the rayon industry from 1990 onward (Campbell et al, ; Du et al, ; Zumkehr et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…Observed atmospheric surface mixing ratios from global and hemispheric averages of NOAA air monitoring sites (Montzka et al, ), as well as annually averaged tropospheric mixing ratios from Jungfraujoch (Lejeune et al, ), show a moderate decline in the 1990s followed by similarly moderate growth in the 2000s (both approximately 1% year −1 ), with relatively little interannual variation. These time trends have been attributed to trends in the anthropogenic inventory, driven by a decline in residential coal in the early 1990s and the decline and growth of the rayon industry from 1990 onward (Campbell et al, ; Du et al, ; Zumkehr et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…The emission factors of the speciated NMHCs, PM, NO x , CO and SO 2 from combustion of raw bituminous coal, which is currently prevalent for cooking and heating in rural areas, have been reported to be 0.56-5.40, 25.49 ± 2.30, 0.97 ± 0.03, 208 ± 5 and 2.43-5.36 g kg −1 , respectively (Du et al, 2016;Liu et al, 2017). Annually burned crop residues and domestic coals were estimated to be 160 Tg (Q.…”
Section: Resultsmentioning
confidence: 99%
“…Our measured emission factors of SO 2 were lower than those reported by Cao et al (2008) and Kim Oanh et al (2015) for rice straw, but higher than those reported by Cao et al (2008) for corn and wheat straw. Due to low sulfur contents in crop straws, the SO 2 emission factors for open burning of crop residues were much lower than those for domestic coal combustion, which were determined to be 2.43-5.36 g kg −1 for raw bituminous coal (Du et al, 2016). Table S1, in which a comprehensive dataset of emission factors measured in this work is included.…”
Section: Oa Production Predictionmentioning
confidence: 99%
“…There are indications of other parts of the OCS budget being underestimated, such as domestic coal combustion (Du et al, 2016). Emissions of biomass burning and direct and indirect anthropogenic emissions have been considered in previous estimates (e.g., 315.5 Gg S yr −1 in Berry et al, 2013, 224 Gg S yr −1 in Kuai et al, 2015, and 219 Gg S yr −1 in Glatthor et al, 2015), but a recent anthropogenic emission estimate by Lee and Brimblecombe (2016) increases this number to 598 Gg S yr −1 , which would already bring sources and sinks closer to agreement.…”
Section: Discussionmentioning
confidence: 99%